Building collective action at crime hot spots: Findings from a randomized field experiment - Weisburd, David (Journal of experimental criminology, 2021)
Abstract Objectives The study examined whether Assets Coming Together (ACT), a policing intervention directed at increasing collective action and collective efficacy at crime hot spots in Brooklyn Park, Minnesota, would have impacts on these outcomes, as well as police legitimacy, crime and fear of crime. Methods We used a block-randomized experimental design in which hot spots of crime were randomly allocated to treatment and control conditions. The treatment condition received the ACT program, and the control condition received normal police response. We analyzed crime data using an ANOVA approach, taking into account treatment and block. We analyzed survey data collected at each hot spot using mixed-effects linear regression models with robust standard errors to account for the nesting of responses within hot spots. Results We find that the intervention increased citizen reporting of collective actions (including collaboration in problem solving and contacts with the police) at hot spots, but it had little impact on general measures of collective efficacy or police legitimacy. Fear of crime increased at the treatment sites. We found that crime reporting was significantly inflated in the treatment sites. Crime outcomes were non-significant without accounting for this reporting inflation, but the treatment areas had a significant crime decrease when adjusting estimates based on reporting inflation. Conclusions Our experimental findings show that collective actions at hot spots can be encouraged through programs like ACT and that ordinary policing resources—patrol officers in this case—can be successfully used to carry out such programs. We find preliminary evidence that the program also impacted crime. At the same time, our study points to a bias in using official crime data to assess outcomes in programs that encourage community collaboration.